Myotonometry and extended field-of-view ultrasound imaging allow reliable quantification of patellar tendon stiffness and length at rest and during maximal load, whereas several restrictions exist for the Achilles tendon - Wegener, F.; Ritterbusch, A.; Saal, C.; Baumgart, C.; Hoppe, M. W. (Frontiers in Sports and Active Living, 2024)
Introduction Stiffness and length are well-established tendon parameters in sports and medicine. Myotonometry and ultrasound imaging are the commonly used methods to quantify these parameters. However, further studies are needed to clarify the reliability of these methods, especially when assessing maximally loaded tendons and when conducted by different experienced investigators. This study aimed to determine the intra- and interrater reliabilities of measuring the stiffness and length of the patellar tendon (PT) and Achilles tendon (AT) using the myotonometry method and the extended field-of-view ultrasound (EFOV-US) technique at rest and maximal load performed by different experienced investigators.